2011
DOI: 10.1007/s00128-011-0493-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Assimilation and Digestive Toxicity in Naïve Grass Shrimp (Palaemonetes pugio) Exposed to Dietary Cadmium

Abstract: Naïve grass shrimp Palaemonetes pugio were pulse-fed cadmium-contaminated meals containing carbon-14, fluorescent or near-infrared markers and analyzed for carbon assimilation efficiency, gut residence time, feces elimination rate, extracellular digestive protease activity or gut pH. Carbon assimilation efficiency (~83%), minimum gut residence time (~435 min) and proventriculus pH (~5.29 to ~6.01) were not impacted significantly by cadmium ingestion. A dose-dependent decrease in feces elimination rate (from ~1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cadmium toxicology has been studied in various aquaculture organisms (Wu et al 2006;Seebaugh et al 2012;Ma et al 2013). and previous studies have demonstrated that Hsps are involved in the defense against cadmium toxicity (Jing et al 2013;Jung and Lee 2013;Mazzei et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium toxicology has been studied in various aquaculture organisms (Wu et al 2006;Seebaugh et al 2012;Ma et al 2013). and previous studies have demonstrated that Hsps are involved in the defense against cadmium toxicity (Jing et al 2013;Jung and Lee 2013;Mazzei et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also observed in shrimp subjected to chronic field exposure, where digestive plasticity may have played a role in maintaining nutrient assimilation (Seebaugh and Wallace 2009;Seebaugh et al 2011). In other studies, AE-14 C% was unresponsive to a pulse of Cd in meals or pre-exposure to dietary Cd for 15 days (Seebaugh 2010;Seebaugh et al 2012). Carbon assimilation by this species does not appear to be correlated with temperature, salinity, or gut transit time (Morgan 1980;Seebaugh et al 2011).…”
Section: Rate Of Casein Hydrolysis -P Pugiomentioning
confidence: 60%
“…Previous studies have demonstrated that mode of internal exposure (i.e., pre-assimilatory vs. post-assimilatory exposure) after metal ingestion can exert differential impacts on end points related to consumer digestion (Seebaugh 2010;Seebaugh et al 2012). In the present work, we have shown that dietary Hg can elicit post-assimilatory impacts on grass shrimp digestion, which may, in turn, influence Hg assimilation during subsequent digestive cycles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations